Assertive Acts in Premier’s Reading Challenge: Portraying an Australian Muslim Writer’s Concerns of the World - Sheila Budi Tania; Zuliati Rohmah (Universitas Brawijaya, 2022)
An interview is a discourse between the interviewer and the interviewee with the goal of exchanging information. Seen from the perspective of speech act’s theory, one of the functions of an interview is to deliver information from the speaker to the hearer where assertive acts are prominent. However, research on assertive acts to date has devoted little attention to the Islamic discourse. Therefore, this present study discusses assertive acts uttered by the guest speaker talking about her work and experiences as a Muslim living in Australia. This current study collected the data from the transcription of a New South Wales Premier’s Reading Challenge interview with Randa Abdel-Fattah episode. This study applied the descriptive qualitative approach using content analysis in approaching data. In analyzing the data, the researchers were indebted to Searle and Kreidlr, especially on their classifications of assertive acts. The results show seven types of assertive acts noticeable in Randa Abdel-Fattah’s responses to the interview with telling as the most often evident act.